2019
DOI: 10.1093/nar/gkz754
|View full text |Cite
|
Sign up to set email alerts
|

Conserved HORMA domain-containing protein Hop1 stabilizes interaction between proteins of meiotic DNA break hotspots and chromosome axis

Abstract: HORMA domain-containing proteins such as Hop1 play crucial regulatory roles in various chromosomal functions. Here, we investigated roles of the fission yeast Hop1 in the formation of recombination-initiating meiotic DNA double strand breaks (DSBs). Meiotic DSB formation in fission yeast relies on multiple protein-protein interactions such as the one between the chromosome axial protein Rec10 and the DSB-forming complex subunit Rec15. Chromatin immunoprecipitation sequencing demonstrated that Hop1 is colocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 81 publications
6
39
2
Order By: Relevance
“…Only once Hop1 is bound to Red1 is the binding site for Mer2 then exposed. Intriguingly, in fission yeast, the zinc-finger of Hop1 has been suggested to be required Mer2 binding 22 , which would be consistent with our model and our data. We were unable to obtain an interaction between Hop1 and Red1I743R in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only once Hop1 is bound to Red1 is the binding site for Mer2 then exposed. Intriguingly, in fission yeast, the zinc-finger of Hop1 has been suggested to be required Mer2 binding 22 , which would be consistent with our model and our data. We were unable to obtain an interaction between Hop1 and Red1I743R in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…We only observe binding between Mer2 and Hop1 in the presence of Red1. This could of course be explained through direct binding to Red1, but Hop1 orthologs have been implicated as the direct interactor of Mer2 orthologs 22,23 . We propose a model whereby Hop1 that is bound to its own closure motif is not competent for Mer2 binding (Figure 4D, left).…”
Section: Discussionmentioning
confidence: 99%
“…All four LinE subunits formed linear structures ( Figures 1A and S1), but the Rec10-GFP linear structures were slightly shorter than the others. In addition, previous studies showed the DNA binding preference of Rec10 is different from those of the other LinE subunits: Rec25, Rec27 and Mug20 are concentrated at DSB hotspots, whereas Rec10 is more uniformly distributed along chromosomes (Miyoshi et al, 2012;Fowler et al, 2013;Kariyazono et al, 2019). Our observation of a…”
Section: Discussioncontrasting
confidence: 49%
“…But another mechanism can remove LinE clusters before MII, allowing the sister chromatids to complete their separation at MII. Several proteins, such as Rec15 and Hop1, interact with both Rec10 and the DSB forming complex (Kariyazono et al, 2019) and may also be involved in LinE structure disassembly.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that HORMAD1/IHO1 [38] plays a role in tethering DSB hotspots marked by H3K4me3 and H3K36me3 to the axis through the interaction with methyltransferase PRMD9 [39][40][41][42][43][44] for the formation of DSB by SPO11/TOPO6BL complex. In yeast, Hop1 [45], a homolog of HORMAD1, localizes to the axis through Red1 and mediates DSB formation by recruiting Mei4/Rec114/Mer2 complex to the axis [46][47][48], suggesting the evolutionally conserved roles for HORMAD1/Hop1 in the initiation of meiotic DSBs.…”
Section: Introductionmentioning
confidence: 99%